Teachers’ Perceptions on Business English Courses of BBS at Tribhuvan University - Budhathoki, Mahendra Kumar (Haimaprabha, 2023)
Curriculum designers do not survey and contemplate the views of the concerned faculty. The experiences, perceptions and knowledge of the faculty are also equally important to the experts of the syllabus designers. The purpose of this study is to explore the teachers’ perceptions on Business English Courses of BBS at Tribhuvan University. This study specifically has explored how teachers perceive the course and implement it in the classroom. This research utilized qualitative method through interviews as a means of information collection. The participants purposively sampled were four Business English teachers from Tribhuvan University. Major findings of the study were as follows: the respondent teachers agreed that overall quality of Business English syllabus was satisfactory because this syllabus was ESP-based course for business students. The teachers complained that the textbook English for Business Studies seemed like a guide book. The teachers suggested to focus on all four language skills and English proficiency, and contents must be from business sectors for business students. Although the research on need analysis seems money and time consuming for Curriculum Development Centre, in the long run it will be rewarding after finding students’ needs and the syllabus’s effect. This study ignites teachers and Dean’s Office of Faculty of Management to do further research to determine the needs and goals of the ESP-based syllabus. Further research are necessary to discover the real needs of BBS students and determine the objectives in Tribhuvan University in Nepal.